Mechanical properties of fire retardant wood-plastic composites: A review - T. C. Mokhena; E. R. Sadiku; M. J. Mochane; S. S. Ray (eXPRESS Polymer Letters)
Wood-plastic composites (WPCs) are a group of emerging and a sustainable class of high-performance materials, consisting of polymers reinforced with wood particulates, having a wide range of applications in the field of building, infrastructure, and transportation. However, the main drawback of the WPCs is their high flammability. Fire retardants usually enhance WPCs’ flame retardancy but at the expense of mechanical properties. This paper reviews the available literature on flame retardant WPCs in developing an optimum condition between the flammability and mechanical properties, i.e., the addition of wood-flour and flame retardant (FR) in order to find a balance between the flammability resistance and their mechanical properties. It concentrates on the recent advances in the mechanical properties and flammability studies of wood flour-polymer composite products. The applications and durability of these flame retardant WPCs with future remarks are also highlighted.